EDUCATIONAL ACTIVITY OF STUDENTS AS DETERMINING FACTOR OF FORMATION CREATIVE PERSONALITY - O.O. Pavlenko (Academy of Cognitive and Natural Sciences, 2007)
The problem of creative personality's formation in conditions of modern higher educational establishment's functioning and restructuring is observed in the article. The need for creative potentials preservation and development as one of the principal tasks of innovative education is stressed. The attention to realization of a student as an activity }s subject, who is able to show his creative (reformative) activity himself in this future profession is paid. In this connection, the use of the group and collective forms of education, the introduction in the educational process are observed.